CHARACTERIZATION OF ISOBATHS IN THE CENOMANIAN RESERVOIR OF THE MUANDA FIELD – IMPLICATIONS FOR OPTIMAL OIL RESOURCE MANAGEMENT - Marlin Agolo Monza; Franck Tondozi Keto; Raphael Matamba Jibikila; Yves Bolokole Mpehenzale; Osée Mayinga Mayinga (Romanian Journal of Petroleum & Gas Technology)
The study of isobaths characterization in the Cenomanian reservoir of the Muanda field focuses on optimizing petroleum resource management. Using geostatistical techniques and numerical analysis methods, the isobaths of the K, J, I and H layers were mapped. The K layer, the most superficial, is 44 meters thick, while the J and I layers reach 48 meters respectively. This research highlights the spatial variability of isobaths, a key factor in understanding the rapid depletion of the reservoir, which is mainly attributed to the presence of argillites. The lithological heterogeneity, characterized by high clay content, influences reservoir permeability, complicating fluid flow and, consequently, well productivity. The study also subdivided the reservoir into distinct zones according to clay content, revealing that the southwestern zone has a clay content of over 57.42%, while the southeastern zone is less clayey, with a content of less than 41.87%. The results underline the importance of a geostatistical approach to resource management, identifying target areas for potential interventions such as hydraulic fracturing. This study thus contributes to a better understanding of reservoir dynamics and to the formulation of appropriate strategies for the sustainable exploitation of petroleum resources in the Muanda region.